Analysis of SCR Based ESD Protection Device with Optimized Low Trigger Voltage for Low Trigger Voltage Applications - Lee, Byung-Seok; Koo, Yong-Seo (Journal of semiconductor technology and science, 2017)
In this paper, the Silicon Controlled Rectifier (SCR)–based ESD protection device is proposed to reduce the trigger voltage, and to increase the ESD robustness. The proposed protection device is composed of the SCR with an additional bridge N+, P+ diffusion region, and LVTSCR. The operation mechanism of the proposed protection device and the DC I-V characteristics are simulated by the Synopsys TCAD process simulator with various design variables. The proposed protection device was fabricated by using a 0.18 BCD process for the evaluatation of the effectiveness in an integrated circuit, TLP characteristics are analyzed, and the human body model (HBM) and machine model (MM) tests were performed. Also, the proposed protection device was examined for thermal characteristics under high temperature (300 k~500 k). In the experimental result, the proposed device had a low trigger voltage of 5.8 V, and 8 kV HBM of ESD robustness. The proposed protection device was fabricated by using 0.18 um BCD process. KCI Citation Count: 0